ZIF‐67 Derived Porous Carbon from Calcination and Acid Etching Process as an Enzyme Immobilization Platform for Glucose Sensing. Issue 3 (10th January 2018) - Shi, Libo; Cai, Xuan; Li, Hong; He, Haiyan; Zhao, Hongli; Lan, Minbo
Abstract: In this work, a metal‐organic frameworks‐based porous carbon was explored for glucose oxidase immobilization and glucose sensing. ZIF‐67 was chosen as the precursors for the calcination treatment. The formed Co nanoparticles induced the graphitization of the carbon during the carbonization, resulting in a good conductivity. The followed HCl treatment partly removed the formed Co nanoparticles to give a larger specific surface area of the porous carbon due to the generated space voids from the dissolved Co nanoparticles. The resulting MOFs‐derived porous carbon show an improved loading performance toward glucose oxidase, and fast electron transfer was also demonstrated. This work proves the MOFs‐derived porous carbon as a novel and outstanding platform for the enzymatic electrocatalysis for the sensors and energy conversion devices. Abstract :